Peranan media sosial dalam pengembangan melek politik mahasiswa - Pradana, Yudha (Jurnal Civics: Media Kajian Kewarganegaraan, 2017)
This research is used quantitative approach and descriptive method. Instrument used by the research is skala Survey of Study Habits and Attitudes questionnaire to describing media social using by students and Likert Scale questionnaire to describing student's political literacy. Data analysis using Rank Spearman Order.The result show that social media used by students 48% good, 26% fair, and 15% poor. Student's political literacy are 36% good, 43% fair, and 21% poor. The role of social media in the development of student's political literacy is 54,79% affected by social media, and 45,21% affected by other factors.